2020
DOI: 10.1111/iej.13381
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical dissolution of nickel‐titanium instrument fragments in root canals of extracted human maxillary molars using a small reservoir of electrolyte

Abstract: Amaral CCF, Ormiga F, Ara ujo OMO, Lopes RT, Gomes JACP. Electrochemical dissolution of nickeltitanium instrument fragments in root canals of extracted human maxillary molars using a small reservoir of electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…According to Amaral et al's study, this time is close to what could be considered clinically acceptable and a good starting point to bypass the fragment. 8 The results presented here showed mean Flconcentrations of 52.76, 98.13 and 48.31 mg/kg in groups 1, 2 and 3, respectively. These values are lower than those in a range from 12.3 to 22.6 g/L, which have been largely applied in dentistry to inhibit dental structure demineralization.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…According to Amaral et al's study, this time is close to what could be considered clinically acceptable and a good starting point to bypass the fragment. 8 The results presented here showed mean Flconcentrations of 52.76, 98.13 and 48.31 mg/kg in groups 1, 2 and 3, respectively. These values are lower than those in a range from 12.3 to 22.6 g/L, which have been largely applied in dentistry to inhibit dental structure demineralization.…”
Section: Discussionsupporting
confidence: 50%
“…In the diffusion tests of the present study, the root canal was filled with 0.02 mL of the test solution, which was maintained in the root canal for two hours. This time was used according to Amaral et al, 8 who observed a significant reduction in the NiTi instrument fragment volume as a consequence of the electrochemical dissolution process in root canals of extracted human maxillary molars using the solution restricted to a small reservoir. According to Amaral et al's study, this time is close to what could be considered clinically acceptable and a good starting point to bypass the fragment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations